A Review of Theories of Expression in the Context of the Development Argument - Appiagyei-Atua, K. (My University, 2007)
The present article examines the subject-matter of freedom of expression. It offers a critical review of the principal perspectives on the subject as propounded by Western philosophers and situates the discussion of the relevance of their views in a non-Western environment. It does so in the context of development and ends up postulating a new paradigm which examines the relationship between freedom of expression and development and the exercise of this freedom, not by individuals qua individuals, but by individuals in a community context. This idea takes into account traditional African approaches to the exercise of freedom of expression. It then applies this developmental, community-oriented perspective of freedom of expression to the promotion of democracy and human rights in emerging states.